(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2017)
In many countries, people have enforced their relation with Government with mobilization – focus on flash mob in internet – and this new kind of citizenship has changed the typical relationship between State and Citizens in a resilient way. According the principle of resilience, democracy must be seen as a social construction that results from new roles. Here we will analyze and discuss on the topic of Resilience using current examples as indigenous movements and the new Constitution of Ecuador and Brazilian streets manifestations in 2013 and 2014. We believe that the relationship between State and Civil Society nowadays must provide conditions to Citizens emancipation and we cannot analyze their relationships without considering the mutual perception as authors of a dialogue in which on has authority powers, the “other” has control powers aiming citizenship.